Maranao folk art survey of forms, designs and meanings - Saber, Mamitua (University Research Center, 1981)
"This monograph deals with a brief but intensive survey of some aspects of Lanao folk art undertaken by the authors for the Institute of Research for Filipino Culture in Mindanao State University. It has value to the Institute's Museum and Folk Art Center concerned with the collection and study of Philippine folk art in the southern regions, especially the Mindanao-Sulu area where the different ethnic groups have preserved their rich cultural heritage from the past generations."--Introduction.